ANALISIS PENGUJIAN PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, RISIKO BISNIS, DAN TINGKAT PERTUMBUHAN TERHADAP LEVERAGE PERUSAHAAN - VIANDGO, YUVITA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Every company has the same goal of making a profit, increase the value of the company, and the welfare of shareholders. However, to achieve these goals is not easy, the competition is getting tougher now, requires companies to work extra hard and new innovations and fresh ideas are needed to make the company different and superior. In addition, the company's capital structure is an important element in achieving success because of capital, how it is used, and the sources are very important for the company. The use of debt and equity a company called leverage will affect the company's capital structure. This study aimed to determine the effect of variable size, profitability, business risk, and growth rate on the level of leverage with companies in the consumer goods industry as its object and the study period for 3 years (2009-2011). This study is the causality with hypothesis. The sampling technique used was purposive sampling, sample totaling 25 companies, the data used are secondary data that the company's financial statements. The analysis technique used is panel data regression with fixed effect models. This analysis is used to see how much influence and direction of influence of each independent variable on the leverage of the company specifically. These results indicate that firm size is positive but not significant effect on leverage. While the rate of growth and the profitability affects leverage is negative and significant, and the business risk positively affect leverage significantly.